South African and International Reference Values for Lung Function and its Relationship with Blood Pressure in Africans - van Rooyen, Yolandi; Huisman, Hugo W.; Schutte, Aletta E.; Eloff, Fritz C.; Du Plessis, Johan L.; Kruger, Annamarie; Van Rooyen, Johannes M. (Heart, lung & circulation, 2015)
In South Africa respiratory diseases are highly prevalent, with cardiovascular disease being a manifestation. However, international reference values for lung function are commonly used, which may not be appropriate to correctly identify reduced lung function. An inverse relationship exists between lung function and blood pressure (BP) but is not investigated extensively in black South Africans. We included 2010 Africans from the PURE (Prospective Urban Rural Epidemiology) study (aged > 35 years) in the North West Province. Spirometry was performed and predicted values for forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were calculated from South African, European and United States prediction equations. With the exception of the European predicted values, all other predicted mean FEV1 and FVC were above 80%. South African reference values displayed the highest percentages of the predicted values for FEV1 and FVC (87.9 and 99.7%, respectively.) BP increased from quintiles five to one for both FEV1 and FVC, (p for trend <0.001). After adjustment the differences remained (p<0.05). South African reference values yielded higher percentages of predicted FEV1 and FVC values than European and US equations suggesting that South African prediction equations may be more useful when investigating lung function in black South Africans. Elevated BP is related to reduced lung function, highlighting the importance in managing both respiratory- and cardiovascular disease.